Bone healing in critical-size defects treated with bioactive glass/calcium sulfate: A histologic and histometric study in rat calvaria - Furlaneto, Flávia A. C. [UNESP]; Nagata, Maria José Hitomi [UNESP]; Fucini, Stephen E.; Deliberador, Tatiana M. [UNESP]; Okamoto, Tetuo [UNESP]; Messora, Michel R. [UNESP] (Wiley, 2007)
Objective: The purpose of this study was to analyze histologically the influence of bioactive glass (BG) with or without a calcium sulfate (CS) barrier on bone healing in surgically created critical-size defects (CSD) in rat calvaria. Material and methods: A CSD was made in each calvarium of 48 rats. They were divided into three groups: C (control): blood clot only; BG: defect filled with BG; and BG/CS: defect filled with BG covered by a CS barrier. Animals were euthanized at 4 or 12 weeks. Formation of new bone was evaluated histomorphometrically. Results: No defect completely regenerated with bone. BG particles were observed in Groups BG and BG/CS at both periods of analysis. The thickness throughout the healing area in Groups BG and BG/CS was similar to the original calvarium, while Group C presented a thin connective tissue in the center of the defect in both periods of analysis. At 4 weeks, Groups C and BG/CS presented significantly more bone formation than Group BG. No significant differences were found between Groups C and BG/CS. At 12 weeks, no significant differences in the amount of bone formation were observed among the three groups. When comparing 4 and 12 weeks, there was a significant increase in new bone formation within groups BG and BG/CS, but not C. Conclusion: BG particles, used with or without a CS barrier, maintained the volume and contour of the area grafted in CSD. However, they did not lead to a significant difference in bone formation when compared with control at 12 weeks post-operative. © 2007 Blackwell Munksgaard.
Keywords: Bioactive; Bone regeneration; Bone substitutes; Calcium sulfate; Glass; Biogran; biomaterial; calcium sulfate; glass; unclassified drug; animal; bone regeneration; cytology; drug effect; male; randomization; rat; skull; Wistar rat; Animals; Biocompatible Materials; Bone Regeneration; Calcium Sulfate; Male; Random Allocation; Rats; Rats, Wistar; Skull